The computation of stationary distributions of Markov chains through perturbations. (1991) - Hunter, Jeffery J.
Abstract : An algorithmic procedure for the determination of the stationary distribution of a finite, m -state, irreducible Markov chain, that does not require the use of methods for solving systems of linear equations, is presented. The technique is based upon a succession of m, rank one, perturbations of the trivial doubly stochastic matrix whose known steady state vector is updated at each stage to yield the required stationary probability vector.